Diagnosis and Management of Portal Vein Thrombosis in Liver Cirrhosis - Kurniawan, Cynthia; Jasirwan, Chyntia Olivia Maurine (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Portal vein thrombosis is formation of thrombus in main portal vein and its branches, that may also affect superior or mesenteric veins. Rebalanced coagulation system and changes in hepatic portal venous flow augment risk of portal vein thrombosis. Modalities to identify portal vein thrombosis include ultrasonography, contrast enhanced Computed Tomography (CT), and Magnetic Resonance Imaging (MRI). The management of portal vein thrombosis in hepatic cirrhosis is challenging due to intricate balance between thrombosis and bleeding complicating treatment decision. Treatment option consisted of close monitoring, anticoagulation, thrombolysis, and trans-jugular intrahepatic portosystemic shunt (TIPS). Anticoagulant options for management of portal vein thrombosis encompass Low Molecular Weight Heparin (LMWH), Vitamin K Antagonist (VKA), and Direct Oral Anticoagulant (DOAC). There is still no consensus regarding the thrombolysis for the management of portal vein thrombosis in cirrhosis due to lack of evidence. TIPS may be considered in portal vein thrombosis with insufficient response or contraindication to anticoagulation, repeated variceal bleeding, and/ or refractory ascites which unable to be controlled by medical or endoscopic management. This review aims to discuss the current update in diagnosis and management of portal vein thrombosis in liver cirrhosis.Keywords: Cirrhosis, portal vein thrombosis, anticoagulant